1989
DOI: 10.1080/00380768.1989.10434751
|View full text |Cite
|
Sign up to set email alerts
|

Studies on saline soils in khon kaen region, northeast thailand I. Physical and chemical properties of saline soils

Abstract: Saline soils occur extensively in Northeast Thailand. As the climate of this region is clearly differentiated into dry and rainy seasons, salts in the groundwater move up and accumulate on the soil surface during the dry season and are leached down with rainfall during the rainy season. In this paper, the physical and chemical properties concerned with salt movement were investigated for the saline soils in the Khon Kaen Region, Northeast Thailand. Changes in the physical and chemical properties with leaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 3 publications
0
26
0
1
Order By: Relevance
“…Islam et al (2014) found most soils had very low amounts of total N. Like other tropical and subtropical soils, Bangladesh soils have long been categorized as poor in soil fertility because of low N supplying capacity (Islam, 1983). Patcharapreecha et al (1989) investigated saline soils contains total nitrogen (0.005-0.043%) contents were very low in all the soils. Several studies have shown that salinity reduces N uptake (Al-Rawahy, Stroehlein, & Pessarakli, 1992) by crops and do not support plant growth due to a higher osmotic pressure in the plant soil system Bhumbla (1977) despite adequate nutrient levels being available in the soil.…”
Section: ) Total Nitrogen (N) Content (%)mentioning
confidence: 85%
See 1 more Smart Citation
“…Islam et al (2014) found most soils had very low amounts of total N. Like other tropical and subtropical soils, Bangladesh soils have long been categorized as poor in soil fertility because of low N supplying capacity (Islam, 1983). Patcharapreecha et al (1989) investigated saline soils contains total nitrogen (0.005-0.043%) contents were very low in all the soils. Several studies have shown that salinity reduces N uptake (Al-Rawahy, Stroehlein, & Pessarakli, 1992) by crops and do not support plant growth due to a higher osmotic pressure in the plant soil system Bhumbla (1977) despite adequate nutrient levels being available in the soil.…”
Section: ) Total Nitrogen (N) Content (%)mentioning
confidence: 85%
“…Uddin and Islam (1998) investigated the Coastal soils of Bangladesh and most soil Organic matter (%) ranges < 2 to > 20. Patcharapreecha et al (1989) investigated saline soils that contain 0.07-0.74% soil OM. Haque (2006) found the pretty low (1.0-1.5%) soil OM content in coastal saline soils.…”
Section: Relation Between Soil Texture and Soil Salinity (Ec) In Paddmentioning
confidence: 99%
“…Patcharapreecha et al (1989) reported that washing with a small amount of water decreased the EC values of these soils drastically.…”
Section: Resultsmentioning
confidence: 99%
“…The sampling sites were KK2 and KK4, which had been studied in detail by Patcharapreecha et al (1989). Japanese paddy soil collected from Anjo Agricultural Experiment Station was used for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…mg kg -1 (Carter and Fanning, Lee et al, 2000;1963;Kim et al, 1988;Jo et al, 1993;Koo et al, 1992;Patcharapreecha et al, 1990;Ryu et al, 2014;Tejedor et al, 2003;Sadegh-Zadeh et al, 2009;Sohn et al, 2010;Son et al,, 1994). 춘다는 다수의 연구결과와 일치하였다 (Fanning and Carter, 1962;Carter and Fanning, 1963;Kim et al, 1988;Kim et al, 1990;Patcharapreecha et al, 1990;Tejedor et al, 2003;Zhang et al, 2008;Sadegh-Zadeh et al, 2009).…”
mentioning
confidence: 99%